2021
DOI: 10.1186/s12882-021-02360-8
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable risk factors of acute kidney injury after liver transplantation: a systematic review and meta-analysis

Abstract: Background Acute kidney injury (AKI) is a common and critical complication of liver transplantation (LT), which is associated with increased morbidity, mortality and health care cost. We aimed to identify modifiable risk factors of AKI after LT. Methods A literature search of Pubmed, EMBASE and Cochrane Databases was performed to identify studies investigating risk factors of AKI after LT. The Newcastle-Ottawa Scale was used to rate study quality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
1
23
1
2
Order By: Relevance
“…One of the important findings in our study was that more renal dysfunction required RRT in the PRS group. In a meta-analysis performed by Zhou et al PRS was identified as one of the AKI risk factors after LT [ 28 ]. Hemodynamic instability during PRS has a major effets on decreased renal blood flow and renal tissue hypoxia, which can play an important role in the development of AKI after LT, on the other hand, PRS not only releases cold and acidotic components from the graft but also releases pro-inflammatory cytokines that trigger the inflammatory response and cause renal tubular injury [ 28 ] .In terms of the need for surgical revision, in the initial period after transplantation, although in our study, bleeding was the most common reason for the need for reoperation in both groups, there was significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important findings in our study was that more renal dysfunction required RRT in the PRS group. In a meta-analysis performed by Zhou et al PRS was identified as one of the AKI risk factors after LT [ 28 ]. Hemodynamic instability during PRS has a major effets on decreased renal blood flow and renal tissue hypoxia, which can play an important role in the development of AKI after LT, on the other hand, PRS not only releases cold and acidotic components from the graft but also releases pro-inflammatory cytokines that trigger the inflammatory response and cause renal tubular injury [ 28 ] .In terms of the need for surgical revision, in the initial period after transplantation, although in our study, bleeding was the most common reason for the need for reoperation in both groups, there was significant difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the risk factors identified in the present research, several other authors have already described that higher MELD scores[ 37 ] were associated with AKI after LT[ 20 , 38 ]. Xu et al [ 21] showed that MELD score > 25 was a predictor of AKI, and in patients with MELD scores > 30, the most required RRT[ 11 , 39 ]. Moreover, in the cirrhosis scenario, the functional renal disorders can be added as risk factors for AKI, such as recipient HRS[ 11 , 23 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [ 21] showed that MELD score > 25 was a predictor of AKI, and in patients with MELD scores > 30, the most required RRT[ 11 , 39 ]. Moreover, in the cirrhosis scenario, the functional renal disorders can be added as risk factors for AKI, such as recipient HRS[ 11 , 23 , 40 ]. Donor marginal liver grafts of ECD were identified elsewhere as a strong predictor of PGD[ 24 - 26 ] and post-LT AKI[ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These intraoperative factors could be the target of possible interventions and prevention strategies for transplant anesthesiologists. 50 The vasoconstrictor terlipressin is used for type 1 hepatorenal syndrome (HRS-1) in many parts of the world outside of the US and is part of the clinical practice guidelines in Europe. Wong and collaborators completed the CONFIRM Study, a phase 3 trial to confirm the efficacy and safety of terlipressin plus albumin in adults with HRS-1.…”
Section: Renal Topicsmentioning
confidence: 99%